Bribes, bullets, and intimidation : drug trafficking and the law in Central America - Bunck, Julie Marie, 1960-; Fowler, Michael Ross (Pennsylvania State University Press, 2012)
"Examines drug trafficking through Central America and the efforts of law enforcement to counter it. Details the routes, methods, and networks involved, while comparing the evolution of the drug trade in Belize, Coast Rica, Guatemala, Honduras, and Panama over three decades"--Provided by publisher.